SOUTHERN TASIKMALAYA ANCIENT SUBMARINE VOLCANO: VESTIGES OF ERUPTIONS AND THEIR DIVERSITY AS GEOLOGICAL HERITAGE - Djafar, Agustina; Suharyogi, Ifan Yoga Pratama; Sari, Rahajeng Ayu Permana; Jayanti, Anita Galih Ringga; Sipayung, Andhy Darmeidi; Pratomo, Indyo (Jurnal Geosains dan Teknologi, 2023)
In the southern Tasikmalaya area West Java Province, Indonesia, there are Tertiary volcanic rocks, with an east-west trending distribution pattern.  Physiographically, this area is included in the southern mountain zone of West Java and is generally composed of tuff and polymic breccias with intercalated of lava and limestone which are grouped into the Jampang Formation and Genteng Members Jampang Formation. The existence of these volcanic and sedimentary rocks of Oligocene – Middle Miocene in the area is an indication of submarine volcano. The purpose of this paper to identify traces of eruptions and submarine volcano products found in the southern Tasikmalaya area, for further assessment of the geological diversity potential as a geological heritage. The method used are field data collection and quantitative data analysis, namely identification of geological heritage based on "Technical Guidelines for the Assessment of Geological Heritage Resources". The submarine volcano products which found in this area are peperite, and basaltic andesite lava at Karang Tawulan Beach, traces of alteration, and hydrothermal mineralization like jasper Panca Tengah, and Cipatujah volcanogenic massive sulphide. This shows that volcanic activities in the southern Tasikmalaya took place continuously from Oligocene to Middle Miocene. From the results of the assessment, the geological diversity in this area has a scientific value of "medium-high".